PERANCANGAN IKLAN LAYANANMASYARAKAT TENTANG CAR FREE DAY DI KOTA PADANG DALAM MEDIA BALIHO - RAJAKU MELIALA, Dr. Budiwirman, M.Pd, Drs. Ismanadi Uska (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Car Free Day is a car-free day which aims to reduce air pollution polluted by motor vehicles and also has a special purpose, namely that people care about the environment that is clean and comfortable